(untitled) (ОБРАЗОВАНИЕ НАУКА И ИННОВАЦИОННЫЕ ИДЕИ В МИРЕ, 2025)
This article examines the concept of Media and Information Literacy (MIL) as a key competence in the digital age. It discusses how MIL enables individuals to access, analyze, evaluate, and create information across various media platforms responsibly and critically. The paper highlights the growing importance of MIL for students, educators, and society, emphasizing its role in combating misinformation, promoting ethical communication, and fostering informed decision-making. Furthermore, the article explores practical strategies for developing MIL skills, including critical thinking, source evaluation, and digital citizenship. The study concludes that strengthening media and information literacy is essential for empowering individuals to participate effectively and safely in today’s information-rich environment.